Inequities in kidney health and kidney care - Vanholder, Raymond; Annemans, Lieven; Braks, Marion; Brown, Edwina A; Pais, Priya; Purnell, Tanjala S; Sawhney, Simon; Scholes-Robertson, Nicole; Stengel, Bénédicte; Tannor, Elliot K; Tesar, Vladimir; van der Tol, Arjan; et al. (Nature reviews. Nephrology, 2023)
Health inequity refers to the existence of unnecessary and unfair differences in the ability of an individual or community to achieve optimal health and access appropriate care. Kidney diseases, including acute kidney injury and chronic kidney disease, are the epitome of health inequity. Kidney disease risk and outcomes are strongly associated with inequities that occur across the entire clinical course of disease. Insufficient investment across the spectrum of kidney health and kidney care is a fundamental source of inequity. In addition, social and structural inequities, including inequities in access to primary health care, education and preventative strategies, are major risk factors for, and contribute to, poorer outcomes for individuals living with kidney diseases. Access to affordable kidney care is also highly inequitable, resulting in financial hardship and catastrophic health expenditure for the most vulnerable. Solutions to these injustices require leadership and political will. The nephrology community has an important role in advocacy and in identifying and implementing solutions to dismantle inequities that affect kidney health.
Keywords: nemoci ledvin; dostupnost zdravotnických služeb; Kidney; lidé; výdaje na zdravotnictví; ledviny; Health Services Accessibility; Health Expenditures; Kidney Diseases; Humans